The Role of the Teacher in Improving the Quality of Learning Through the Teaching Freedom Platform - Hidayat, Erik; Muharizal, Muharizal (Journal of Engineering Education and Pedagogy, 2023)
The Merdeka Mengajar Platform is an application that can be used by teachers to implement the independent curriculum in learning. The Merdeka Mengajar Platform is also a platform that teachers can use to improve their quality as teachers and learners in achieving the goals of the independent curriculum. The Merdeka Mengajar platform offers five items divided into categories such as teacher quality development and learning activities. The development products to improve teacher quality include: Inspirational Videos, Independent Training, Proof of My Work. The use of the Merdeka Mengajar Platform is the right method to enhance the development of teacher competence, innovation and creativity. With various features that can make it easier for teachers to develop their teaching skills, it is necessary to socialize regarding the use of the Merdeka Mengajar Platform, so that the purpose of the Merdeka Mengajar Platform as a means of improving teacher quality in developing learning can truly be realized